2020
DOI: 10.1007/s13311-019-00830-4
|View full text |Cite
|
Sign up to set email alerts
|

DREADD Activation of Pedunculopontine Cholinergic Neurons Reverses Motor Deficits and Restores Striatal Dopamine Signaling in Parkinsonian Rats

Abstract: The brainstem-based pedunculopontine nucleus (PPN) traditionally associates with motor function, but undergoes extensive degeneration during Parkinson's disease (PD), which correlates with axial motor deficits. PPN-deep brain stimulation (DBS) can alleviate certain symptoms, but its mechanism(s) of action remains unknown. We previously characterized rats hemi-intranigrally injected with the proteasomal inhibitor lactacystin, as an accurate preclinical model of PD. Here we used a combination of chemogenetics wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 89 publications
(154 reference statements)
2
27
1
Order By: Relevance
“…Based on this evidence, we expected dual lesion to reduce forepaw stepping and L-DOPA-mediated motor improvement. Whereas others using a less severe PD phenotype observed effects of stimulating PPN cholinergic neurons on akinesia (Pienaar et al, 2015;Sharma et al, 2020), we observed no effects of lesion on stepping at baseline or on L-DOPA. Unlike research by Pienaar et al (2015), in our severe 6-OHDA lesion model, PPN control of SNc DA release is likely lost.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Based on this evidence, we expected dual lesion to reduce forepaw stepping and L-DOPA-mediated motor improvement. Whereas others using a less severe PD phenotype observed effects of stimulating PPN cholinergic neurons on akinesia (Pienaar et al, 2015;Sharma et al, 2020), we observed no effects of lesion on stepping at baseline or on L-DOPA. Unlike research by Pienaar et al (2015), in our severe 6-OHDA lesion model, PPN control of SNc DA release is likely lost.…”
Section: Discussioncontrasting
confidence: 99%
“…PPN cholinergic neurons stimulate locomotion (Xiao et al., 2016) and ameliorate deficits in forepaw akinesia by normalizing nigrostriatal DA transmission (Pienaar et al., 2015; Sharma et al., 2020). Furthermore, combining SNc DA lesion and PPN ACh lesion produces more severe lesion than either technique alone (Bensaid et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, such further studies may be best placed by utilizing an in vivo system, since the balance of iron homeostasis is maintained through a dynamic equilibrium between systemic tissues, and hence an animal system will allow for a comparison between various body compartments, while molecular iron regulators identified so far have been shown to operate in man as well as rodents (Wallace 2016). In this regard, our previous work showed that rats that had received a unilateral nigral stereotaxic injection of lactacystin accurately mirror the behavioural and neuropathological deficits shown by PD patients (Pienaar et al 2015a, b;Sharma et al 2020).…”
Section: Discussionmentioning
confidence: 93%